Climate Change Perception, Action, and Hope among High School Students: Insights for Science Education - Espinola, Esmeth; Roleda, Lydia (Universitas Negeri Semarang, 2025)
Current climate data shows that human-driven climate change is now affecting both nature and people irreversibly. Several studies have explored the perception, actions, and hopes of individuals regarding climate change, but few have analyzed their relationship. This study aimed to analyze students’ perceptions, actions, and hopes, examine the structural relationships among these variables, and determine the mediating role of hope. A quantitative survey was conducted to statistically analyze students’ perceptions, actions, and hopes. Results reveal strong agreement among students about the reality and anthropogenic causes of climate change. In terms of actions, students have relatively more participatory actions than leadership actions towards the environment. When it comes to hope, students generally believe in their own ability to act, but there are a few who exhibit hopelessness due to the complexity of climate change. Structural equation modeling reveals a positive relationship between perception and hope (r = 0.62), indicating that awareness promotes optimism about solutions. Moreover, mediation and path estimates revealed the mediating role of hope, suggesting that perception influences action through hope. These findings emphasize the need for climate change education to bridge the attitude-behavior gap by fostering a sense of hope and positive instruction to increase students’ mitigative actions.